Psychophysical Characteristics of the Premenstrual Period - Staničić, Ana; Jokić-Begić, Nataša (2010)
Aim of this study was to investigate psychophysical characteristics of the premenstrual period in regard to the period following menstruation. Psychophysical characteristics are defined as assessments of the physical state (fatigue, breast tenderness, bloating and lack of sleep), emotional sense (happiness, anger, sadness, irritability, anxiety and distraction) and general assessments of physical attractiveness and satisfaction with oneself. Diary of psychophysical characteristics was designed for this study as well as a socio-demographic questionnaire and a menstrual cycle calendar. 51 healthy, non-help-seeking women, aged 21-46 kept a diary of psychophysical characteristics a week before menstruation and four days one week after the onset of menstruation, during two menstrual cycles. The premenstrual period is characterized by the intensification of negative emotional states, the decline of positive emotional states, and the worsening of the general self-image through the decline of the perception of physical attractiveness and satisfaction with oneself. In conclusion, the premenstrual period is not marked only by the mood-swings but also by the changes in the cognitive representation of self.
Projekt MZOS
ENG